2001
DOI: 10.1136/ard.60.6.577
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of autologous stem cell transplantation in systemic sclerosis: procedure related mortality and impact on skin disease

Abstract: Background-Systemic sclerosis (SSc, scleroderma) in either its diVuse or limited skin forms has a high mortality when vital organs are aVected. No treatment has been shown to influence the outcome or significantly aVect the skin score, though many forms of immunosuppression have been tried. Recent developments in haemopoietic stem cell transplantation (HSCT) have allowed the application of profound immunosuppression followed by HSCT, or rescue, to autoimmune diseases such as SSc. Methods-Results for 41 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
161
1
19

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(191 citation statements)
references
References 29 publications
3
161
1
19
Order By: Relevance
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is also used as a new therapy for the treatment of severe autoimmune diseases such as multiple sclerosis, systemic sclerosis and systemic lupus erythematosus (13)(14)(15). Autologous HSCT has also been performed on three patients with Behçet's disease (16)(17)(18) (2,5,11,12 …”
Section: Discussionmentioning
confidence: 99%
“…For example, agents such as bleomycin, BCNU (carmustine), and radiation that are complicated by pulmonary fibrosis would not be the logical conditioning agents for a disease such as scleroderma, mixed connective tissue disease, or dermatomyositis in which a major cause of death is related to pulmonary fibrosis and pulmonary artery hypertension. [1][2][3][4] Conditioning regimen design should also avoid agents that could damage organ-specific stem cell compartments that may contribute to organ repair after the disease remits. The effect of conditioning agents on tissue-specific stem cell viability and proliferative potential is unknown.…”
Section: Rationale For Design Of Autologous Autoimmune Hsct Regimensmentioning
confidence: 99%